Antidepressants as risk factor for ischaemic heart disease: case-control study in primary care - Hippisley-Cox, Julia (BMJ, 2001)
OBJECTIVES: To determine whether antidepressants are a risk factor for ischaemic heart disease and to compare the risk for different subgroups of antidepressants and individual antidepressants. DESIGN: Case-control study. SETTING: Nine general practices recruited from the Trent Focus Collaborative Research Network. PARTICIPANTS: 933 men and women with ischaemic heart disease matched by age, sex, and practice to 5516 controls. MAIN OUTCOME MEASURE: Adjusted odds ratio for ischaemic heart disease calculated by logistic regression. RESULTS: Odds ratios for ischaemic heart disease were significantly raised for patients who had ever received a prescription for tricyclic antidepressants even after diabetes, hypertension, smoking, body mass index, and use of selective serotonin reuptake inhibitors had been adjusted for (1.56; 95% confidence interval 1.18 to 2.05). Patients who had ever taken dosulepin (dothiepin) had a significantly raised odds ratio for ischaemic heart disease after adjustment for confounding factors and use of other antidepressants (1.67, 1.17 to 2.36). There was no significant increase in the odds ratios for amitriptyline, lofepramine, and selective serotonin reuptake inhibitors in multivariate analysis. Increasing maximum doses of dosulepin were associated with increasing odds ratios for ischaemic heart disease. Similarly, there was a significant positive trend associated with increasing numbers of prescriptions of dosulepin (adjusted odds ratio 1.52 for 1 prescription, 1.39 for 2-3, and 1.96 for ⩾4, P<0.002). CONCLUSION: There is good evidence for an association between dosulepin and subsequent ischaemic heart disease and for a dose-response relation.